Processing of resid-VGO mixtures in FCC: Laboratory approach - Devard, Alejandra Veronica (2009)
In order to validate a new method for the evaluation of resid in the laboratory, the conversion of a mixture of 10% of an ATR resid with a FCC VGO feedstock was assessed with two equilibrium catalysts of the conventional and resid type at 550 °C and contact times up to 25 s, and compared with the conversion of the base VGO and ATR under the same conditions. The experiments were performed in a batch, fluidized bed CREC Riser Simulator laboratory reactor. Under these circumstances, the overall conversions of the mixture were not very different from those of the base VGO in the case of the resid catalyst, but increased up to 5% points with the conventional and more active catalyst. For a given conversion level, the yields of the main hydrocarbon groups like dry gas, LPG and gasoline did not change significantly, and were consistent with the reactivity of the pure reactants (VGO and ATR), that showed essentially the same selectivities. The higher coking trend of the ATR was observed moderately in the case of the most active catalyst. The most important changes were noticed in the composition of the various products; for example, with both catalysts, the gasoline cuts produced by the ATR-VGO mixture were less aromatic and more olefinic than those obtained with the pure VGO. It was shown in this new laboratory method that in order to achieve realistic results in the evaluation of the addition of resid to a FCC feedstock, it is necessary to consider simultaneously the mixture intended, the proposed catalyst and the operative conditions.